Processing speed, working memory, and executive functions: independent or inter-related predictors of general intelligence - Frischkorn, Gidon T.; Schubert, Anna-Lena; Hagemann, Dirk (Intelligence, 2019)
Both working memory capacity (WMC) and processing speed (PS) have been discussed as important covariates of individual differences in intelligence. Recent results indicated that especially latencies of ERP components associated with higher-order processing (P2, N2, and P3) may share up to 80% of variance with individual differences in intelligence. WMC has a similar predictive power and thus these two processes cannot explain individual differences in intelligence independently. The current study explores in how far individual differences in executive functions (EFs) may bridge the gap between WMC and PS as predictors of intelligence. We recruited 101 participants who completed three EF tasks - one for each of the three executive functions shifting, updating, and inhibition. Additionally, we assessed participants' intelligence, WMC, and PS. Results showed that only variance of behavioral RTs consistent across manipulations in the EF tasks was related to WMC, PS, and intelligence. The variance specific to the manipulations in EF tasks was small and showed no consistent correlations with each other or with any of the three covariates. These results suggest that EF tasks capture mostly manipulation-unspecific cognitive processes. Hence, individual differences in the impairment due to additional executive processing demands cannot explain why WMC and PS are related predictors of individual differences in intelligence.